A Design of an Electric Light Control Device Using Arduino Uno Microcontroller-Based Short Message Service - Siregar, Ivana Maretha; Siagian, Nancy Florida; Siregar, Victor Marudut Mulia (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
This study aims to design a tool that can control electric lights remotely. The wastage of using lights often occurs due to the difficulty of the occupants of the house in controlling the lighting, especially when they have to leave the house due to various activities. Lighting needs to be controlled to turn on or not when you want to travel for a long time. In addition, lighting needs to be controlled to significantly reduce the service life of the lamp because it is on continuously. This remote light control system can make it easier for users to cut electricity usage. An electric light controller designed using SMS (Short Message Service) based on the Arduino Uno Microcontroller. This system only applies if the condition of the AC voltage originating from the local PLN is ON. System control is managed using the Atmega328 Arduino Uno Microcontroller. The language used for programming is C/Arduino language, and this tool works on GSM communication systems, especially SMS services. The result of designing this tool is that the user can control (ON/OFF) the lights without being limited by time and place as long as the cellular network is reachable.